2021
DOI: 10.1186/s12889-021-11432-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers and caregivers’ perspectives on factors responsible for persistent malnutrition of under 5 children in Buhweju district, South Western Uganda; a phenomenological qualitative study

Abstract: Background Unacceptably high levels of childhood malnutrition have been registered in all regions of Uganda over the years. Buhweju district alone contributed 46% prevalence of childhood malnutrition to the 47.8% estimated national prevalence for the whole of western Uganda in 2014. This study assessed health provider and caregiver opinions on factors responsible for persistent malnutrition among under five children in Engaju and Nyakishana sub counties. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
2
3
0
Order By: Relevance
“…In this study poverty was mentioned as predisposing factor for severe acute malnutrition. This finding was in line with a study done in Uganda [ 33 ]. This may be due to relatively similar socio-economic status of the study participants of Uganda and Ethiopia.…”
Section: Discussionsupporting
confidence: 94%
“…In this study poverty was mentioned as predisposing factor for severe acute malnutrition. This finding was in line with a study done in Uganda [ 33 ]. This may be due to relatively similar socio-economic status of the study participants of Uganda and Ethiopia.…”
Section: Discussionsupporting
confidence: 94%
“…This could be because some parents have tight schedules and do not get enough time to provide adequate care. This is in agreement with a study done in Nyakishana and Engaju in Buhweju district, South Western Uganda, where 83% of the caretakers for children below five years reported to be working for long hours in their gardens and tea farms that were very far from their homes (Abaasa, et al, 2021).…”
Section: Practices Of Caretakers Towards Malnutrition Among Children ...supporting
confidence: 92%
“…However, the results of this study showed a slightly higher Cure rate than the one observed in a similar study done in Ghana in 2015 with a Cure rate of 33.6% (Mahama et al, [13]). The reason for this could be due to the number of factors like differences in the socioecomic status, geographical challenges as well as variation in the clinical expertise of the health care providers as observed by Abaasa and colleagues (Abaasa, et al, [31]).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Kabale district is approximately 420 km from Kampala the capital city of Uganda (Kabale district statstics report, [11]) and has an estimated population size of 248,700 people of whom 120,000 are males and 128,700 are females according to Uganda bureau of statistics 2020, Kabale. As a district, food insecurity, low socioeconomic staus, sub-optimal infant and young feeding practices, lack of quality drinking water and geographical challenges are some of the risk factors for malnutrition (Bakusuba, et al, [30] and Abaasa, et al, [31]).…”
Section: Study Sitementioning
confidence: 99%